Craniosacral therapy in welfare and autonomous nervous system of fighters of mixed martial arts: cases study. - Amorim, Diane Nogueira Paranhos; Mendonça, Lia Medeiros Brandim; Matos, Ludmilla Karen Brandão Lima de; Shimizu, Iara Sayuri (Manual Therapy, Posturology & Rehabilitation Journal, 2014)
Introduction: The Craniosacral Therapy uses tender and accurate touches to diagnose and treat the craniosacral system. The Mixed Martial Arts athletes are exposed at risk of injury during competitions, which can affect your welfare. The Craniosacral Therapy improves the functioning of the Central and Autonomic Nervous System, that promotes relaxation, sense of welfare and homeostasis in the body. Objective: to evaluate the effect of Craniosacral Therapy in welfare and Autonomic Nervous System in Mixed Martial Arts fighters. Method: We conducted a case study by analyzing the heart rate and general welfare of 05 Mixed Martial Arts fighters, eight sessions with Craniosacral Therapy, using respectively a frequency Polar RS800 and a Range of Subjective Well-Being for collection data, posteriorly it was submitted to the calculation of mean and standard deviation and “T Studant” test to compare the data before and after the treatments. Results: The initial evaluation of the athletes showed a high subjective well-being, that remained after the therapy. There was a statistically significant increase in one of the athletes with respect to positive affect (from 4.048 ± 0.5896 to 4.429 ± 0.5071). As for the negative affects three increased the score. There was a statistically significant reduction (p <0.001) between the initial and final heart rates in each service, with averages of 68.50 and 63.28 respectively. Conclusion: The Craniosacral Therapy increases the activity of the parasympatic nervous system, promoting decreased heart rate, providing better coronary flow and that alone is not sufficient to determine an increase or decrease of well-being.